EFFECT OF WORK SPIRIT AND WORK MOTIVATION ONEMPLOYEE ENGAGEMENT IN THE TANJUNGPINANG BUMI RESTAURANT (VEGETARIAN) - Ikram Jerry Setiawan; Indrayani Indrayani; Muammar Khaddafi; Yanita Yanita; Henny Irawati (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2022)
This research aims to know the influence of the variable work spirit and motivation towards Employee Engagement at the restaurant Bumi Maitri (Vegetarian) Tanjungpinang. The study used quantitative associative methods with a population of 42 respondents at the Maitri Earth Restaurant (Vegetarian) Tanjungpinang. The results of the study were Y = 50,503 + 0, 461X1 + 0, 552X2 + E and the value of coefficient of determination (R2) amounted to 0.245 or 24.5%. The results of a variable T-test of the work spirit towards employee engagement at the obtained value probability Signifkasi of 0.002 < 0.05 and the value of Thitung 3.309 > this 1.68385.. Work motivation variables against employee engagement at the obtained probability signified value of 0,009 < 0.05 and Thitung value 2.756 > this 1.68385. The results of this study showed that the working motivation variable partially affected the employee engagement in the restaurant Bumi Maitri (Vegetarian) Tanjungpinang. The test results of the working spirit and the motivation of work affect employee engagement with the value of Fcalculate 7.641 > Ftabel3, 24th. The value of Adjusted R Square is 0.245 or 24.5%. The remaining 75.5% is influenced by other variables not examined in this study.